Analisis Pengambilan Keputusan Kebijakan Dalam Penanganan Perjudian Online - Naila Ainaiya; Alya Hadziqo Sae Saiffy; Revienda Anita Fitrie (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Policy decision making in dealing with online gambling is based on several factors. This journal article analyzes policy decision making in handling online gambling in Indonesia by policy makers. This research uses descriptive research methods with a literature study approach. Analysis theory is based on decision making according to George R. Terry and Brinckloe, such as intuition, experience, facts, authority and logic. The research results obtained are that in Indonesia, the criminal law approach to online gambling is contained in Article 27 paragraph (2) of Law Number 11 of 2008 concerning Information and Electronic Transactions. The government considers the interests of society, sustainability and the long-term impact of the decisions taken. Transparency and accountability in decision making is the government's responsibility to ensure fair and sustainable policies. Thus, the government's role as a decision maker involves many complex factors and considerations to achieve good policies that have a positive impact on society.